2005
DOI: 10.1002/hep.20701
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a histological scoring system for nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is characterized by hepatic steatosis in the absence of a history of significant alcohol use or other known liver disease. Nonalcoholic steatohepatitis (NASH) is the progressive form of NAFLD. The Pathology Committee of the NASH Clinical Research Network designed and validated a histological feature scoring system that addresses the full spectrum of lesions of NAFLD and proposed a NAFLD activity score (NAS) for use in clinical trials. The scoring system comprised 14 his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

116
8,369
5
174

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9,020 publications
(8,951 citation statements)
references
References 24 publications
116
8,369
5
174
Order By: Relevance
“…After validation, the test maintained a suitable capacity to distinguish NASH from NAFL (AUROC of 0.79 ± 0.04) with a good specificity of 0.81, indicating that it may perform well for NASH diagnosis because of low false‐positive errors 45. This test divided patients classified as NASH borderline between the two diagnostic categories (NAFL and NASH), which agrees with previous studies 21, 22. Analysis of the impact of the stage of each of the histologic features of the NAS system on the accuracy of the diagnostic test revealed that, in general, the error rate of NASH diagnosis ranged between 20% and 40% for the different values of the features of the NAS system and between 30% and 60% for the different score values of fibrosis.…”
Section: Discussionsupporting
confidence: 86%
“…After validation, the test maintained a suitable capacity to distinguish NASH from NAFL (AUROC of 0.79 ± 0.04) with a good specificity of 0.81, indicating that it may perform well for NASH diagnosis because of low false‐positive errors 45. This test divided patients classified as NASH borderline between the two diagnostic categories (NAFL and NASH), which agrees with previous studies 21, 22. Analysis of the impact of the stage of each of the histologic features of the NAS system on the accuracy of the diagnostic test revealed that, in general, the error rate of NASH diagnosis ranged between 20% and 40% for the different values of the features of the NAS system and between 30% and 60% for the different score values of fibrosis.…”
Section: Discussionsupporting
confidence: 86%
“…(B) Liver MALAT1 expression levels are significantly associated with the full spectrum of NAFLD histologic severity. The severity of histologic features was graded according to scores described by Brunt et al12 and Kleiner et al11 as indicated in the Methods section. Horizontal lines refer to mean value.…”
Section: Resultsmentioning
confidence: 99%
“…Degree of steatosis was assessed according to the system developed by Kleiner et al11 based on the percentage of hepatocytes containing macrovesicular fat droplets. NASH and NAFLD activity score were defined as reported11, 12; NASH was defined as steatosis plus mixed inflammatory cell infiltration, hepatocyte ballooning and necrosis, Mallory's hyaline, and any stage of fibrosis, including absent fibrosis 11, 12. In patients with chronic HCV, liver histopathology was scored according to Ishak's fibrosis grading and staging system 13…”
Section: Methodsmentioning
confidence: 99%
“…All biopsies where read by two experienced liver pathologists who were blinded to patient details. All biopsies where graded according to NAFLD activity score and fibrosis stage according to Kleiner et al32 …”
Section: Methodsmentioning
confidence: 99%